The New Curriculum Implementation in Indonesia: A Study in Two Primary Schools - Yulianti, Kartika (International Journal about Parents in Education, 2023)
The new 2013 curriculum has just been implemented recently in Indonesia from primary to secondary school levels. There are a lot of criticisms towards the implementation, especially in the schools’ readiness to apply the new curriculum in the real classroom. This study aims to investigate the role of school leaders in the new curriculum implementation. Several aspects were also examined: teacher professional development with regards to the curriculum implementation, how schools involve parents prior and during the curriculum implementation, supporting factors for the implementation and factors that hinder the success of the new curriculum implementation. Data were gathered from school leaders, teachers, and parents. The findings show that school leaders in these schools play an important role by exercising transformational leadership and shared instructional leadership. Continuous teacher professional development and professional learning community are other important factors for the success of the new curriculum implementation. Time constraints and limited resources are reported to be the hindering factors. The findings show that albeit schools acknowledge the importance of parental involvement in students’ learning, schools have not given adequate support that parents need in order to be fully involved in their children’s learning.